THE INTEGRATED PETROPHYSICAL EVALUATION USING OPEN HOLE LOGS AND CORE DATA FOR KUHLAN RESERVOIR IN AL-SABATAYN BASIN - AL-HASANI, ABDULLAH (2017)
The subsurface Kuhlan Formation is widely exposed in the Sabatayn Basin, western Yemen, which is an alternative reservoir rock in the basin. Integrated petrophysical and petrographic analyses were performed on the Kuhlan clastic rocks. These types of analyses yield valuable information and knowledge about reservoir characteristics and significant hydrocarbon reserves. Through this study, thorough investigations have been conducted to evaluate the petrophysical reservoir properties, identify grain sorting along with the clay type and mineral volumes using well logs coupled with core data. Core samples were collected from two key wells and their results were used to determine the reservoir properties and bulk mineralogical composition and, additionally, to calibrate the well log results from five un-cored to the cored wells. The lithology and mineral composition of the well logs and petrographic studies indicate that the Kuhlan Formation is primarily composed of sandstone that contains quartz, orthoclase, plagioclase, illite, and calcite minerals. The quartz mineral is dominant followed by feldspar as the second most abundant mineral in this formation. The Kuhlan Formation sandstones are classified (based on standard rock classification schemes) into arkose, sub-arkose and feldspathic lithofacies and deposited in a transitional continental environment. Petrographically, the Kuhlan sandstones are poorly sorted and coarse-grained and contain high percentages of detrital quartz and feldspar grains with a variable range of matrix and cement contents. Based on the depositional environment controls and the pore occluding cements, the reservoir quality of the Kuhlan sandstone ranges between good to poor reservoir quality. The Kuhlan Formation has arkosic and sub-arkosic sandstones that result in a good reservoir quality with a significant increase of the permeability and intergranular porosity. This is attributed to the coarse-grained texture, high percentages of detrital quartz, slightly well sorted texture and the low degree of matrix and cements. In contrast, the Kuhlan Formation feldspathic sandstone has poor reservoir quality due to the poor sorting texture, pore space occluding clayey groundmass, and carbonate cement.